(untitled) (Revista Argentina de Musicología, 2019)
A Subjective Pathway to an Objective Modernity. Boris Asafyev and the Avatars of Musicology in the Soviet Union Soviet musicologists worked side by side with composers and were in charge of defining the ways in which works should be composed under the precepts of Socialist Realism. In this sense, studying the functioning of musicology in the Soviet Union becomes an important input for a better understanding of the compositional field as well of the cultural dynamics of the soviet regime. This article focuses on the figure of Boris Asafyev, the founder of musicology in the Soviet Union. It analyzes one of his first texts written during the revolutionary context, in which the musicologist raises a series of questions that will lay the foundations of what would later be his main musicological concepts, such as intonatsia or simfonizm, concept that would be incorporated into Socialist Realism. The hypothesis developed here is that there is in the young musicologist Asafyev a concern for the relationship between the new revolutionary society and the Russian musical heritage that is closely linked to a concern early shown by the revolutionaries themselves, namely the development of a Soviet modernity that should be parallel to the construction of a communist society. This concerns will reappear with force in the 1930s and 1940s when the Soviet system reaches its most defined physiognomy.